Bone marrow mesenchymal stem cell-derived exosomes alleviate skin fibrosis in systemic sclerosis by inhibiting the IL-33/ST2 axis via the delivery of microRNA-214. (May 2023) - Xie, Lihu; Long, Xiaoping; Mo, Meili; Jiang, Jinmei; Zhang, Qingxiu; Long, Mei; Li, Mei
Abstract: Interleukin (IL)− 33 is a tissue-derive proinflammatory cytokine that promotes fibrosis in systemic sclerosis (SSc). microRNA (miR)− 214 expression has been elaborated to be downregulated in SSc patients and exert anti-fibrotic and anti-inflammatory effects. This study elucidates the role of bone marrow mesenchymal stem cell-derived exosome (BMSC-Exos)-delivered miR-214 in SSc and the relationship between this miR and IL-33/ST2 axis. SSc clinical samples were obtained to evaluate levels of miR-214, IL-33, and ST2. Primary fibroblasts and BMSC-Exos were extracted, followed by the co-culture of PKH6-labeled BMSC-Exos and fibroblasts. Subsequently, Exos extracted from miR-214 inhibitor-transfected BMSCs were co-cultured with TGF-β1-stimulated fibroblasts, after which the expression of fibrotic markers, miR-214, IL-33, and ST2, as well as fibroblast proliferation and migration, was determined. A skin fibrosis mouse model was induced with bleomycin (BLM) and treated with BMSC-Exos. Collagen fiber accumulation, collagen content, α-SMA expression, and IL-33 and ST2 levels were examined in BLM-treated or IL-33-knockout mice. IL-33 and ST2 were upregulated and miR-214 was downregulated in SSc patients. Mechanistically, miR-214 targeted IL-33 and blocked the IL-33/ST2 axis. BMSC-Exos delivering miR-214 inhibitor augmented proliferation, migration, and fibrotic gene expression in TGF-β1-stimulated fibroblasts. Similarly, IL-33 induced migration, proliferation, and fibrotic gene expression in fibroblasts via ST2. In BLM-treated mice, IL-33 knockout suppressed skin fibrosis, and BMSC-Exos delivered miR-214 to suppress the IL-33/ST2 axis, thus mitigating skin fibrosis. Conclusively, BMSC-Exos alleviate skin fibrosis through the blockade of the IL-33/ST2 axis by delivering miR-214. Highlights: BMSC-exosomal miR-214 inhibits fibroblast growth, migration, and collagenation. miR-214 targets and negatively regulates IL-33. IL-33 knockout retards fibrotic progression of mouse skins. IL-33 induces fibroblast growth, migration, and collagenation via ST2. BMSC-Exo delivers miR-214 to inhibit skin fibrosis by suppressing IL-33/ST2.